KEPUASAN PELANGGAN SEBAGAI HASIL DARI E-SERVICE QUALITY, BRAND IMAGE, DAN PROMOSI PADA PENGGUNA E-COMMERCE - Yahya Yahya; Endang Ranitawati (J-MACC, 2025)
The development of e-commerce in Indonesia is experiencing rapid growth, one of which is evidenced by the increasing number of users on the Lazada platform. In facing increasingly competitive market competition, customer satisfaction becomes an important aspect that service providers must pay attention to. This research aims to analyze the influence of e-service quality, brand image, and promotion on customer satisfaction among Lazada e-commerce users. This type of research is classified as quantitative research. The population in this study is active users of the Lazada e-commerce platform in the Sidoarjo area. Because the population size is not known for certain (infinite population), the sample determination was carried out using the Lemeshow formula, resulting in a sample size of 96 respondents. The sampling technique used is purposive sampling, with primary data collection through questionnaires. Data were analyzed using multiple linear regression analysis with the help of SPSS version 25 software. The regression analysis results showed that the variables of e-service quality, brand image, and promotion have a positive and significant impact on customer satisfaction. These findings underscore the importance of improving e-service quality, brand image, and effective promotion in enhancing customer satisfaction among Lazada e-commerce users.